HOW IS THE SHOCK OF THE MACRO ECONOMICS VARIABLES AND WORLD OIL PRICE EFFECTED THE YIELD OF INDONESIA GOVERNMENT BOND INDEX (INDOBEXGB)? - Nurlia Rahmatika (Media Ekonomi, 2019)
This study aims to measure how is the shock of the macro economics variables and world oil price effected the yield of indonesia government bond index (INDOBEXGB). The research methodology used is quantitative method uses time series data. The source of the data derived with monthly data and secondary data from Bank Indonesia (BI), Central Bureau of Statistics (BPS), Indonesia Bond Pricing Agency (IBPA) and Bloomberg. This research is analyzed by using Vector Error Correction Model (VECM) since there is cointegrated variables which could be seen in Trace Statistic and Max-Eigenvalues Statistic is greater than Critical Value. The result of the analysis shows that the shock of macro economics variables money supply and forex reserves give a negative and significant effect to yield on Indonesia Government Bond Index (INDOBEXGB). Whereas the shock of macro economics variables consumer price index, BI rate, exchange rate, and world oil prices each give a positive and significant effect to Indonesia Government Bond Index (INDOBEXGB).